Selection of IPM Geothermal Drilling Contractor Through a Merit Point System Using the Analytical Hierarchy Process - Effendi, Afif (Universitas Dr. Soetomo, 2019)
One method of evaluating the procurement is a merit point system (value system). In a merit point system price is one of the evaluation criteria, with the understanding that the more complex technical requirements and the more difficult to compare bid proposals, the lower the price weights. In general, the total value for technical bids is higher than price bids. At the auction using the merit point system, there are two main things that greatly affect the results of procurement, namely the determination of technical weighting and the price that will be used when evaluating bids and the method of weighing technical bids. When this is done correctly and appropriately, the company will get the right contractor in accordance with needs and can avoid the opportunity to commit fraud or corruption in the process of procurement. For this reason, the authors conduct research on the determination of technical weight and price as well as the method of weighting technical offerings with a case study of the selection of contracting IPM Geothermal Drilling through the Analytical Hierarchy Process (AHP) approach where the results of the study indicate that the AHP can assist the Procurement Planner to determine the technical weight and price as a reference for evaluating bids through the Merit Point System. AHP also helps the Procurement Implementer to rank technical bids during the technical evaluation. Keywords: merit point system, analytical hierarchy process, IPM Geothermal Drilling